Teaching the cultural and creative industries: An international perspective. (May 2019) - O'Connor, Justin; Gu, Xin; Vickery, Jonathan
Dedicated to the memory our late colleagues, Dr Anna Upchurch (1957–2016) and Dr Lorraine Lim (1980–2017), both of whom attended the symposium from which this Special Issue emerged (Prato, September 2016), and both of whom were to make valuable contributions.